Prognostic value of late gadolinium enhancement in cardiac MRI of non-ischemic dilated cardiomyopathy patients - Behera, Dibya Ranjan (Indian Heart J, 2020)
BACKGROUND: The role of late gadolinium enhancement (LGE) in cardiac MRI (CMR) as prognostic marker in non-ischemic dilated cardiomyopathy (NIDCM) is evolving. OBJECTIVE: To study the effect of LGE in the prognosis of NIDCM patients. METHODS: 112 consecutive NIDCM patients, who underwent CMR, were prospectively followed up for 745 ± 320 days. Primary end point was occurrence of MACE {composite of all-cause mortality, resuscitated cardiac arrest, sustained ventricular tachycardia (VT)/appropriate ICD shock, heart failure (HF) hospitalization}. RESULTS: LGE was present in 44 out of 112 patients (39%). The primary end point (MACE) was significantly higher in LGE + ve group compared to the LGE –ve group (72.7% vs. 29.4%; p < 0.0001). Similarly, cardiac mortality (9.1% vs 2.9%; p < 0.049), VT (13.6% vs. 2.9%; p < 0.031), HF hospitalization (63.6% vs. 30.9%; p < 0.001) were significantly more in LGE + ve group. In univariate model, LGE demonstrated the strongest association with MACE (Hazard ratio [HR] = 2.96 [95% CI 1.685 to 5.201; p < 0.0001). LGE extent of >14% of LV predicted MACE with 90.6% sensitivity and 86% specificity. HR of LGE extent >14% of LV for MACE is 6.12; p < 0.01. LGE was associated with MACE irrespective of its location, pattern or distribution. Multivariate model showed LGE and its extent >14% of LV volume were strongest predictor of MACE. CONCLUSION: LGE and its extent >14% predicts adverse cardiac events in NIDCM irrespective of LVEF and LGE location, pattern or distribution. This study emphasises the role of CMR in risk stratification of NIDCM patients and guiding therapy.